Strengthening Administrative Structures to Enhance Community-Partnered Research - Seccombe-Hett, Pippa (Scholarship@Western, 2024)
Post-secondary institutions across Canada are grappling with how to advance reconciliation and equity in education and research. This challenge is amplified in northern Canada, where northern residents have long sought equity in the Arctic and northern research ecosystems, yet the population has historically been excluded from research programs and research leadership. This paper is focused on exploring how a community college in northern Canada should invest in developing institutional support for research and expanded research capacity as it transforms into a polytechnic university. The community college serves a remote population where the majority of residents are Indigenous, and the institution needs to develop capacity in a way that supports both Indigenous self-determination in research and the regional aspirations of expanded research leadership. A solution is proposed that uses transformative and inclusive leadership approaches to guide the development of research services and capacity at the college in partnership with Indigenous and community organizations through the co-development of a partnership framework. The Dissertation-in-Practice (DiP) presents a change implementation plan to develop the proposed solution in collaboration with Indigenous partner organizations. This plan describes how the college can establish institutional support for Indigenous self-determination in research and build research capacity grounded in equity and partnership. Ultimately, this DiP suggests developing a partnership framework to guide the co-development of research capacity in collaboration with Indigenous community partner organizations to empower, strengthen, and uphold a network of community-led research partnerships.